DECREASE IN THE CONTENT OF REACTIVE OXYGEN SPECIES DURING INACTIVATION OF THE RESPIRATORY COMPLEX I IN ARABIDOPSIS CELLS - Vladislav I. Tarasenko; Elena Y. Garnik; Vladimir N. Shmakov; Yuri M. Konstantinov (Siberian Journal of Life Sciences and Agriculture, 2022)
Background. The mitochondrial electron transport chain, in particular the respiratory complex I, is one of the main sources of reactive oxygen species (ROS) in living cells. Suppression of the complex I activity in human cells through chemical inhibition or mutations that disrupt the functionality of this complex leads to a significant increase in the content of ROS. The complex I mutants are also known for plants; however, it is still not clear whether the suppression of the activity of this complex leads to an increase in the level of ROS and the development of oxidative stress.